Pemanfaatan Cangkang Telur Ayam sebagai Sumber CaO: Studi Karakterisasi menggunakan Fourier Transform Infrared Spectroscopy (FTIR - Marinda Afifatu Zahra; Irfan Ashari Hiyahara; Husna Syaima (Jurusan Kimia FMIPA UNMUL, 2025)
This research aims to utilize chicken eggshell waste as a raw material for producing calcium oxide (CaO) through a simple calcination method. Eggshells, which are mostly composed of calcium carbonate (CaCO₃), were calcined at 900°C for one hour. The resulting material was then characterized using Fourier Transform Infrared Spectroscopy (FTIR) to identify the presence of specific functional groups. The FTIR results showed a strong absorption peak at 602.14 cm⁻¹, indicating the presence of Ca–O bonds, which confirms the formation of CaO. However, additional peaks associated with hydroxyl (–OH) and carbonate (CO₃²⁻) groups were also detected, suggesting that some residual Ca(OH)₂ and CaCO₃ remained in the sample. This indicates that the calcination process was not fully complete, and further optimization may be necessary to improve the purity of the CaO obtained.